Deaf people : evolving perspectives from psychology, education and sociology - Andrews, Jean F., 1951-; Leigh, Irene, 1944-; Weiner, Mary Thelma (Boston : Allyn and Bacon, 2004)
Book is an examination of the psychology of the deaf community through history, current topics, and the personal experiences of the authors, two of whom are Deaf.
Includes bibliographical references (p. 259-284) and index.
Keywords: Deaf; Deafness -- Psychological aspects; Deaf -- Means of communication; Deaf -- Education